The memory of the people : custom and popular senses of the past in early modern England - Wood, Andy, 1967-; Cambridge eBooks (Cambridge : Cambridge University Press, 2013)
Did ordinary people in early modern England have any coherent sense of the past? Andy Wood's pioneering new book charts how popular memory generated a kind of usable past that legitimated claims to rights, space and resources. He explores the genesis of customary law in the medieval period; the politics of popular memory; local identities and traditions; gender and custom; literacy, orality and memory; landscape, space and memory; and the legacy of this cultural world for later generations. Drawing from a wealth of sources ranging from legal proceedings and parochial writings to proverbs and estate papers, he shows how custom formed a body of ideas built up generation after generation from localized patterns of cooperation and conflict. This is a unique account of the intimate connection between landscape, place and identity and of how the poorer and middling sort felt about the world around them.
Reformation, custom and the end of medieval England -- Custom and popular memory -- Rights, resources, and social alignments -- Topographies of remembrance -- Textual and verbal ways of remembering -- The politics of popular memory -- Epilogue: resources of hope: working-class memory in rural England.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Customary law -- England; Collective memory -- England; Electronic books